The Effects of Visual Auditory Kinesthetic Learning Style as Technique in Improving Studentsâ Writing Ability - Litta, Lista (ELT WORLDWIDE, 2015)
The objectives of this research were to investigate whether VAK learning style as a technique has significant effects in improving studentsâ writing ability and the studentsâ interest in VAK learning style as a technique in studying English writing.This research employed quasi experimental design. The population of this research was the eleventh grade students of Science Program SMA Negeri 1 Bontomarannuin academic year 2014/2015.This research used cluster random sampling.The sampleconsisted of 60 students that belonged to two groups: 30 students in the experimental andcontrol group.The data was collected by using writing test and questionnaire.The findings showed that there was an improvement on the studentsâ writing ability after the treatment. The studentsâ result of posttest of experimental group was more significantly improved than the studentsâ result of posttest of control group by the mean score 73.2 > 58.1.The difference of both scores was statistically significant based on the t-test value at significant level 0.05 in which the P-value is lower than the significant level (0.0001 < 0.05).The mean score of the studentsâ interest in the experimental group was 91.63 and it was categorized as strongly interested. Key words: VAK Learning Style, Writing